Analisis Pengaruh Kepuasan Kerja Dan Gaya Kepemimpinan Terhadap Kualitas Pelayanan Publik Di Rumah Sakit Umum Daerah (Rsud) Kefamenanu Dengan Motivasi Kerja Sebagai Variabel Intervening - Anita Lassa; Agustinus Longa Tiza (Jurnal Administrasi dan Kebijakan Publik, 2021)
S Service quality relates to conditions related to services, people, processes and the environment where the quality is determined when the delivery of public services takes place. There are many factors that can af ect the quality of public services including leadership, supervision, performance, job satisfaction and employee motivation. However, it is not known exactly what factors consistently af ect the improvement of the quality of public services. This study aims to analyze the ef ect of leadership style and job satisfaction on work motivation and service quality and to analyze the ef ect of work motivation on service quality at Kefamenanu regional public hospital. The research method used is a survey research method. The research data were analyzed quantitatively through the multivariate structural equation model (SEM) technique using the IBM SPSS AMOS program. Hypothesis testing proves that job satisfaction has an ef ect on job satisfaction because the probability (P) value is zero point zero zero seven which is smaller than zero point zero fifty; leadership style has no ef ect on work motivation because the probability (P) value is zero point one hundred and sixty six which is greater than zero point zero fifty; job satisfaction has an ef ect on service quality because the probability (P) value is zero point zero ten which is smaller than zero point zero fifty; leadership style has no ef ect on the quality of public services because the probability (P) value is zero point zero eighty one which is greater than zero point fifty; and work motivation af ects the quality of public services where the probability value (P) is zero point zero zero three which is smaller than zero point zero fifty.